Prospect of Combination and Sequential Therapies for Postmenopausal Osteoporosis - Liu, Hao; Li, Binbin (Current Pharmaceutical Design, 2017)
Background: Osteoporosis is a systemic bone disease, which is associated with the osteoporotic fracture. Along with prolonged life expectancy, the fracture risk increases dramatically with age. So far, it is usually the first choice to using antiresorptive agents. However, current clinical therapeutic treatments are not enough to inhibit the long-term bone loss and the rising risk of bone fractures. Recently, combination and sequential therapies with anti-osteoporosis drugs have become an inevitable trend. Objective: The purpose of this review is to summarize the present knowledge related to the combination and sequential therapies with anti-osteoporosis drugs. Methods: All articles published in PubMed until 2016 on the combination and sequential therapies with antiosteoporosis drugs were reviewed and the relevant literature was described in this review. Results: As the first-line therapy for osteoporosis, the long-term safety and efficacy on bisphosphonate, teriparatide, and new anti-osteoporosis drugs are ongoing concerns. Combination or sequential therapies of boneforming agents and anti-resorptive agents, or two kinds of anti-resorptive agents, or strontium ranelate and other anti-osteoporosis agents have the advantages on BMD compared with monotherapy. Conclusion: So far, it is still an important public health strategy to therapy on the osteoporosis and related fracture. Alternatively, the combination and sequential therapies with anti-osteoporosis drugs are promising approaches for prevention and treatment of osteoporosis and have far-reaching significance.
Keywords: sequential therapy